2015
DOI: 10.1682/jrrd.2014.09.0216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prosthetic prescription after major lower-limb amputation

Abstract: Abstract-We describe prosthetic limb prescription in the first year following lower-limb amputation and examine the relationship between amputation level, geographic region, and prosthetic prescription. We analyzed 2005 to 2010 Department of Veterans Affairs (VA) Inpatient and Medical Encounters SAS data sets, Vital Status death data, and National Prosthetic Patient Database data for 9,994 Veterans who underwent lowerlimb amputation at a VA hospital. Descriptive statistics and bivariates were examined. Cox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…The cause for this delay cannot be identified by our data. However, the time to the first prosthesis in our material is clearly shorter than the mean of 145 days reported from the United States (Resnik and Borgia 2015). A positive trend could be noted in the registry with decreasing numbers of days to first TTA prosthesis, from md 79 days during the first years of registration (year 2011-2013) to md 56 days (year 2017-2018).…”
Section: Discussioncontrasting
confidence: 54%
“…The cause for this delay cannot be identified by our data. However, the time to the first prosthesis in our material is clearly shorter than the mean of 145 days reported from the United States (Resnik and Borgia 2015). A positive trend could be noted in the registry with decreasing numbers of days to first TTA prosthesis, from md 79 days during the first years of registration (year 2011-2013) to md 56 days (year 2017-2018).…”
Section: Discussioncontrasting
confidence: 54%
“…However, most studies [30][31][32][34][35][36] had a small sample size and/or did not report outcomes for different amputation levels. Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively. While Davie-Smith et al [29] analyzed age effects separately for transfemoral and transtibial amputations, Resnik et al [33] reported only a combined age coefficient.…”
Section: Epidemiologymentioning
confidence: 95%
“…Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively. While Davie-Smith et al [29] analyzed age effects separately for transfemoral and transtibial amputations, Resnik et al [33] reported only a combined age coefficient. Hence, we applied data from Davie-Smith et al [29].…”
Section: Epidemiologymentioning
confidence: 95%
See 2 more Smart Citations